2020
DOI: 10.1016/j.heliyon.2020.e05429
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the vividness of mental imagery and eidetic imagery in people with intellectual disability (ID) in comparison with typically developing (TD) individuals

Abstract: Background: Mental imagery (MI) has been described as the "ability to simulate in the mind information that is not currently being perceived by the sense organs" (Moran, 2012, p. 166). The vividness of mental imagery has been defined as the clarity, brightness, or intensity of an image as reported by the individual (Marks, 1973). There are many studies conducted on vividness in typically developing (TD) individuals, however, no attempt has been made either to assess the vividness of mental imagery in people wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The main limitation of our study is that the sample is not large enough for comparisons across subgroups, or for investigation of the risk behavior of individuals with aphantasia (those with no mind’s eye) or with hyperphantasia (whose mental images are as vivid as actual visual perception). While aphantasia has been associated with impaired imagery across multiple sensory domains (including auditory, olfactory and gustatory imagination) 35 , 36 , and with intellectual disability 37 , we are not aware of a study that relates it to choice behavior. Such an investigation would require a more targeted participant recruitment 38 .…”
Section: Discussionmentioning
confidence: 99%
“…The main limitation of our study is that the sample is not large enough for comparisons across subgroups, or for investigation of the risk behavior of individuals with aphantasia (those with no mind’s eye) or with hyperphantasia (whose mental images are as vivid as actual visual perception). While aphantasia has been associated with impaired imagery across multiple sensory domains (including auditory, olfactory and gustatory imagination) 35 , 36 , and with intellectual disability 37 , we are not aware of a study that relates it to choice behavior. Such an investigation would require a more targeted participant recruitment 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study [50] found no significant differences in VMI vividness or eidetic imagery ability in people with intellectual disability compared to typically developing individuals. (i) People with ID experience and engage with mental imagery across different sensory modalities; (ii) The clarity, detail and richness of the images is notable.…”
Section: The Recent Period: 2000-2023 Mental Imagery In People With I...mentioning
confidence: 91%
“…Another recent study [ 50 ] found no significant differences in VMI vividness or eidetic imagery ability in people with intellectual disability compared to typically developing individuals.…”
Section: Recent Period (2000–2023)mentioning
confidence: 99%
“…The vividness of mental imagery refers to the clarity, brightness, or intensity of an image as reported by the individual [ 36 ]. Previous studies have shown that the higher levels of vividness in negative mental imagery are associated with greater distress [ 35 , 37 ].…”
Section: Introductionmentioning
confidence: 99%